Tinjauan Transaksi Crypto Currency Berbasis Keabsahan Kontemporer Syariah - Muntafiah; Syamsul Bakri; Amin Rais (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Cryptocurrency is very often found in almost every economic activity, especially on the basis of modern applications. This study aims to provide an understanding of how cryptocurrency is reviewed according to sharia which is packaged contemporary. This study uses a qualitative approach by utilizing descriptive analysis. Cryptocurrency is seen by the majority of the public as a very ordinary system. Therefore, cryptocurrencies have different properties from stocks and electronic money (e-money) because it is very difficult to find out the contents and/or ownership status and there is no official legality in Indonesia. Understanding the research above is very important to know the limits that have been determined in engaging in the realm of sharia-based business. Keywords: Contemporary; Cryptocurrency; Sharia